2004
DOI: 10.1094/phyto.2004.94.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Enhances the Accumulation of Diterpenoid Phytoalexins in Rice: A Potential Mechanism for Blast Resistance

Abstract: Although several reports underscore the importance of silicon (Si) in controlling Magnaporthe grisea on rice, no study has associated this beneficial effect with specific mechanisms of host defense responses against this fungal attack. In this study, however, we provide evidence that higher levels of momilactone phytoalexins were found in leaf extracts from plants inoculated with M. grisea and amended with silicon (Si(+)) than in leaf extracts from inoculated plants not amended with silicon (Si(-) ) or noninoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
0
24

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(233 citation statements)
references
References 28 publications
9
198
0
24
Order By: Relevance
“…However enhanced disease resistance cannot be explained solely by physical barrier mechanism. It has been reported that Si-induced plant resistance can be also related to increased activity of defense related enzymes such as POD and PPO as well as higher accumulation of antifungal compounds such as phytoalexins (Borel et al, 2005;Fawe et al, 1998;Rodrigues et al, 2004). Therefore, further studies are needed to clarify this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However enhanced disease resistance cannot be explained solely by physical barrier mechanism. It has been reported that Si-induced plant resistance can be also related to increased activity of defense related enzymes such as POD and PPO as well as higher accumulation of antifungal compounds such as phytoalexins (Borel et al, 2005;Fawe et al, 1998;Rodrigues et al, 2004). Therefore, further studies are needed to clarify this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, this protective role was attributed to the accumulation of silica in the leaves, which was believed to interfere with pathogen penetration into the epidermal cells (12). This hypothesis of a passive role, as a mechanical barrier, has been contradicted by reports of protection against root pathogens and by evidence of resistance being induced by Si in plants challenged by pathogens (13)(14)(15). These latest results have exacerbated the confusion surrounding the elusive role of Si in plant biology.…”
mentioning
confidence: 99%
“…Rachilla of the wheat plant also produced prickle hairs, fiber cell, dendriform phytoliths and epidermal cells (Table 1). In the last few decades the procedure of phytolith counts showed a great relevance [dendriform phytoliths (32,33), rod shaped phytolith 3 (34), hairs (35), epidermal cell (36)] and rachilla prickle hairs (37) fiber cell (38), dendriform phytoliths (39) and epidermal cells (40,41) in phytolith studies and has been used by many phytolith researchers [1,46]. We have also used this procedure in a fixed observed area of the slides and after counting we observed that the highest silicified cells were present in leaf blade followed by the awn, leaf sheath, lemma, rachilla and stem (Fig.…”
Section: Transparency and Dry Ash Technique Of Phytolith Extractionmentioning
confidence: 99%
“…The role of silicon is reported to reduce the effects of salt stress, drought stress, metal toxicity, nutrient imbalance and radiation damage [4,8,9,13,44,49,50]. Silicon reportedly increases crop quality and yield, protects the plants against fungal infection, insects, pest attack and increases disease resistance [5,17,26,27,38]. Silicon can also alleviate imbalance between zinc and phosphorus supply as well as decrease the toxic effect of aluminum in hydroponic culture in several species [3,9,44,56].…”
Section: Introductionmentioning
confidence: 99%